Arachidonic Acid Has Anti-Inflammatory and Anti-Diabetic Actions In Vitro and In Vivo. (29th May 2020) - Das, Undurti
Abstract: Objectives: To evaluate the effect of arachidonic acid (AA) in the pathobiology of chemical-induced type 1 and type 2 diabetes mellitus in experimental animals. Methods: In vitro studies were performed using RIN 5F cells and animal studies in 3–4 week old Wistar rats. Alloxan and streptozotocin (STZ) were used to induce type 1 diabetes and STZ employed to induce type 2 diabetes mellitus. RIN5F cell proliferation was measured using MTT assay. Establishment of alloxan and STZ-induced diabetes in animals was confirmed by measuring plasma glucose levels. Plasma insulin, IL-6, TNF levels were measured by ELISA. Expression of cyclo-oxygenase-2, lipoxiygenase, NF-kB and IkB genes was performed in pancreatic and adipose tissues. Results: Alloxan and STZ-induced cytotoxicity to RIN5F cells was inhibited by arachidonic acid that was not blocked by both COX and LOX enzymes. Alloxan and STZ-induced type 1 diabetes mellitus and STZ-induced type 2 diabetes was prevented by arachidonic acid treatment. Plasma levels of glucose, insulin, IL-6 and TNF and expressions of NF-kB, IkB, COX-2, LOX in pancrreatic and adipose tissues and lipocalin-2 in adipose tissue were restored to normal by arachidonic acid treatment. AA treatment enhanced plasma lipoxin A4 (LXA4) levels. LXA4 also prevented both type 1 and type 2 diabetes induction by STZ. Conclusions: AA prevented the development of both type 1 and type 2 diabetes mellitus in Wistar rats and protected pancreatic beta cells form the cytotoxicity of alloxan and STZ. AA showed strong anti-inflammatory actions. AA seems to bring about its anti-inflammatory and anti-diabetic actions by enhancing LXA4 formation. Funding Sources: None.